2010
DOI: 10.1007/s00431-010-1357-6
|View full text |Cite
|
Sign up to set email alerts
|

A young boy with diffuse hyperpigmentation and delayed puberty

Abstract: An 18-year-old male patient had presented with diffuse hyperpigmentation after birth and with adrenal insufficiency syndrome since childhood. After puberty, no secondary sexual signs developed. Laboratory examination showed an extremely high concentration of serum triglycerides (9.14 mmol/L) and plasma adrenocorticotropic hormone (>275 pmol/L), however, a low concentration of plasma free cortisone (<25.1-67.6 nmol/L). Abdomen computed tomography detected atrophy of both adrenals glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Lecube et al [3] first reported the successful treatment of LyH using azathioprine in a patient who failed corticosteroid treatment, and subsequently other authors have reported success with azathioprine [4].…”
mentioning
confidence: 98%
“…Lecube et al [3] first reported the successful treatment of LyH using azathioprine in a patient who failed corticosteroid treatment, and subsequently other authors have reported success with azathioprine [4].…”
mentioning
confidence: 98%